2017
DOI: 10.5269/bspm.v35i3.30008
|View full text |Cite
|
Sign up to set email alerts
|

The characterization of generalized Jordan centralizers on algebras

Abstract: In this paper, it is shown that if A is a CSL subalgebra of a von Neumann algebr and φ is a continuous mapping on A such that (m + n + k + l)φ(A 2 ) − (mφ(A)A + nAφ(A) + kφ(I)A 2 + lA 2 φ(I)) ∈ FI for any A ∈ A, where F is the real field or the complex field, then φ is a centralizer. It is also shown that if φ is an additive mapping on A such that (m + n + k + l)φ(A 2 ) = mφ(A)A + nAφ(A) + kφ(I)A 2 + lA 2 φ(I) for any A ∈ A, then φ is a centralizer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Vukman [22] showed that an additive mapping T : R → R, where R is a 2-torsion free semiprime ring, satisfying 2T (x 2 ) = T (x)x + xT (x) for all x ∈ R, is a centralizer. To read more about centralizers, we refer the readers to some recent papers [2,3,6,7,13,14,15,19,20,21,23], where further references can be found. So far, many mathematicians have investigated Jordan centralizers on triangular rings (or algebras) with unity, see, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Vukman [22] showed that an additive mapping T : R → R, where R is a 2-torsion free semiprime ring, satisfying 2T (x 2 ) = T (x)x + xT (x) for all x ∈ R, is a centralizer. To read more about centralizers, we refer the readers to some recent papers [2,3,6,7,13,14,15,19,20,21,23], where further references can be found. So far, many mathematicians have investigated Jordan centralizers on triangular rings (or algebras) with unity, see, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al ( [10]) proved that a Jordan centralizer on a CSL subalgebra of a von Neumann algebra is a centralizer. Chen et al ( [11]) proved that an additive mapping on a CSL subalgebra of a von Neumann algebra such that ( + + + ) ( 2 ) − ( ( ) + ( ) + ( ) 2 + 2 ( )) ∈ F for any ∈ A is a centralizer. Lately several authors investigated ( , )− Jordan centralizers or their related mappings on rings and algebras.…”
Section: Introductionmentioning
confidence: 99%